2020
DOI: 10.3389/fpsyt.2020.00690
|View full text |Cite
|
Sign up to set email alerts
|

The Cards and Lottery Task: Validation of a New Paradigm Assessing Decision Making Under Risk in Individuals With Severe Obesity

Abstract: was significantly associated with general, but not eating disorder psychopathology. The CLT showed moderate test-retest reliability after one year in weight-stable individuals and was sensitive to change in those undergoing obesity surgery. Conclusions: This study identified the CLT to be a highly promising, new complex measure of short-and long-term decision making with good reliability and validity in individuals with severe obesity. Future studies should assess its association with the IGT and predictive va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 86 publications
(116 reference statements)
0
6
0
Order By: Relevance
“…Reduced sensitivity to monetary losses has also been demonstrated in individuals with sIUDs (e.g., [ 71 ]). Unlike in other tasks, such as the IGT, in the CLT, high loss sensitivity went along with worse performance [ 46 ]. Correspondingly, reduced loss sensitivity can have beneficial effects on CLT performance (as choosing the beneficial option sometimes comeswith immediate losses), which could potentially compensate for deficits arising from weaknesses in cognitive functions in individuals with sIUDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced sensitivity to monetary losses has also been demonstrated in individuals with sIUDs (e.g., [ 71 ]). Unlike in other tasks, such as the IGT, in the CLT, high loss sensitivity went along with worse performance [ 46 ]. Correspondingly, reduced loss sensitivity can have beneficial effects on CLT performance (as choosing the beneficial option sometimes comeswith immediate losses), which could potentially compensate for deficits arising from weaknesses in cognitive functions in individuals with sIUDs.…”
Section: Discussionmentioning
confidence: 99%
“…In this CLT version, performance is negatively associated with impulsivity and positively associated with working memory performance, logical reasoning, and need for cognition in the normal population [ 44 ]. CLT performance has further been shown to be negatively associated with psychopathological aspects such as symptoms of depression, difficulties in emotion regulation, severe obesity, and symptoms of attention-deficit/hyperactivity disorder [ 46 ]. In a recent study on social-networks-use disorder, we found that individuals with problematic social-networks use showed deficits in executive functions, but not in CLT performance [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…The chance of winning this jackpot could be influenced by the choices the participants made during the game: apart from a particular amount of money, some cards showed either a star or bomb symbol, with stars increasing the probability of winning the lottery and bombs deteriorating the probability of winning the lottery. For every participant, the number of advantageous decisions (NAD) reaching from 0 to 36 was calculated with lower scores representing riskier decision making that focuses on positive short-term consequences, despite future negative effects [ 36 , 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…Schäfer et al ( 34 ) developed the card lottery task (CLT) to examine risk-taking in individuals with severe obesity. The task requires selecting cards from decks with conflicting short- and long-term consequences.…”
Section: Introductionmentioning
confidence: 99%
“…This task aimed to resolve a frequent criticism derived from IGT and delay discounting (DDT) in that they do not tackle the conflict between immediate vs. long-term consequences of choices at the same time. Analysis of risk-taking performance of individuals with severe obesity ( 34 ), showed that risk-taking performance as measured by CLT was sensitive to changes (i.e., decrease in the number of risky choices) in risk behavior in participants who underwent obesity surgery.…”
Section: Introductionmentioning
confidence: 99%